Genres discursifs et attentes rhétoriques en Faculté des lettres : de l'acquisition des littératies universitaires à leur évaluation - Béguelin, Victoria; Jeanneret, Thérèse (My University, 2017)
At the end of the Bachelor degree, students of a Faculty of Arts in Switzerland must master the diverse academic written discursive genres necessary to produce and to convey knowledge in the language they study. Teachers must provide them with keys to improve their writing skills – in terms of form as well as content – by a meaningful assessment. This paper presents the device set up at the Faculty of Arts of the University of Lausanne allowing both students' acquisition of written academic literacy and teachers' assessment. Mainly based on a set of descriptors that defines academic genres' main features, the device leads students to autonomously apprehend the notion of genre, to have specific goals in terms of academic writing, to practice self-assessment and to improve their skills through the revision and rewriting of their texts.